Aesthetic and functional rehabilitation with Alumina: a case report - Alves, Ricardo Holanda; Venâncio, Gisely Naura; Meira, Joyce de Figueiredo; Toda, Carina; Conde, Nikeila Chacon de Oliveira; Bandeira, Maria Fulgência Costa Lima (Brazilian Dental Science, 2016)
All-ceramic restoration of anterior teeth is a challenging clinical situation for which a variety of all-ceramic systems are available. The aim of this study is to present a case report of the construction of two single-unit metal-free fixed prostheses in anterior teeth. A 30-year-old male patient came to the Faculty of Dentistry, Federal University of Amazonas, concerned about his teeth. Elements 11 and 12 were endodontically retreated and fiberglass intracanal retainer posts were inserted. Dental crowns were prepared using the silhouette technique. The crowns were cemented with resin cement. The patient was very satisfied with his new smile and the aesthetic rehabilitation of the anterior teeth provided by the treatment. Keywords: Aesthetics; Oral rehabilitation; Dental porcelain.